1994
DOI: 10.1128/aac.38.6.1363
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of vancomycin-, ampicillin-, and aminoglycoside-resistant Enterococcus faecium bacteremia in an adult oncology unit

Abstract: An outbreak of bacteremia caused by Enterococcus faecium with high-level resistance to vancomycin (MIC of > or = 256 micrograms/ml), ampicillin (MIC of > or = 64 micrograms/ml), and gentamicin or streptomycin (MIC of > or = 2,000 micrograms/ml) occurred in an adult oncology unit from June 1991 to May 1992. Active surveillance for the presence of this organism in stool or perianal cultures was begun in September 1991. Between June 1991 and May 1992, seven patients with bacteremia and 22 noninfected carriers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
1
3

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(154 citation statements)
references
References 27 publications
7
143
1
3
Order By: Relevance
“…The most frequent risk factors found included vancomycin use, cephalosporin use, highacuity illness, and immunosuppression. [3][4][5][6] In our study of liver transplant recipients, some of these factors were also found. However, we also identified frequent biliary tract manipulation as a risk factor, suggesting that recipients with biliary complications were at a greater risk for invasive infection.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The most frequent risk factors found included vancomycin use, cephalosporin use, highacuity illness, and immunosuppression. [3][4][5][6] In our study of liver transplant recipients, some of these factors were also found. However, we also identified frequent biliary tract manipulation as a risk factor, suggesting that recipients with biliary complications were at a greater risk for invasive infection.…”
Section: Discussionsupporting
confidence: 63%
“…2 Other centers have identified several risk factors for VREF infection, including empirical broad-spectrum antibiotic therapy, prolonged vancomycin therapy, prolonged hospitalization, and immunosuppression. [3][4][5][6][7] From August through November 1993, 8 liver transplant recipients developed infections with VREF in our institution. While undertaking an epidemiology study, microbiological studies were also performed.…”
mentioning
confidence: 99%
“…Resistance to vancomycin is generally associated with resistance to aminoglycosides and ampicillin making these organisms virtually untreatable with commonly utilized antimicrobial chemotherapy. 15,16 At present, VRE is a common intestinal colonizer among hospitalized individuals. 5 Vancomycin-resistant E. faecium has been isolated increasingly among patients in intensive care units.…”
Section: Tablementioning
confidence: 99%
“…However, Ent. faecium has attracted special attention for its more recent association with clinical infections together with its disposition to acquire multiresistance against antibiotics (Gordon et al 1992;Gray et al 1994;Montecalvo et al 1994), a resistance often associated with conjugative plasmids (Leclercq et al 1989;Evers et al 1996).…”
Section: Introductionmentioning
confidence: 99%